1997
DOI: 10.1038/sj.bmt.1700996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclosporin A on hepatitis C virus infection in bone marrow transplant patients

Abstract: Summary:mechanisms of the onset of hepatitis after BMT in patients with positive HCV antibody. The hepatitis C virus (HCV) infection has, in general, been considered not to affect liver function severely durCase reports ing the course of bone marrow transplantation (BMT) except for late hepatitis which coincided with a decrease Case 1 in immunosuppressive therapy. We examined serial sera of two patients with positive HCV antibody who A 32-year-old woman underwent allogeneic BMT from a underwent allogeneic BMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 1 publication
2
19
0
1
Order By: Relevance
“…Conceivable targets of the Ca 2ϩ /calcineurin pathway include the NFAT-driven, anergy-associated genes (50) and the MAP kinase phosphatases, which inhibit JNK activity by dephosphorylation (31,46). Notably, treatment with cyclosporine A has been demonstrated to reduce the viral load during anti-HCV therapy (1,36). Whereas cyclosporine A is normally used for the suppression of allograft reactions, its inhibitory effects on NFAT can also prevent the acquisition of an anergic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivable targets of the Ca 2ϩ /calcineurin pathway include the NFAT-driven, anergy-associated genes (50) and the MAP kinase phosphatases, which inhibit JNK activity by dephosphorylation (31,46). Notably, treatment with cyclosporine A has been demonstrated to reduce the viral load during anti-HCV therapy (1,36). Whereas cyclosporine A is normally used for the suppression of allograft reactions, its inhibitory effects on NFAT can also prevent the acquisition of an anergic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered reports have noted the effectiveness of CsA treatment in patients with HCV. [19][20][21] Notably, it was recently reported that combination therapy of IFN-␣ and CsA was more effective in HCV than IFN-␣ monotherapy. 22 In the setting of liver transplantation for hepatitis C, during which CsA is given as an immunosuppressant, there have been conflicting reports regarding the efficacy of CsA.…”
Section: Discussionmentioning
confidence: 99%
“…4 Projections about these risks have been based on case reports and studies of patients with a survival rate of about 10 years, some of them significantly differing in regard to the importance of the HCV in the post-BMT. [4][5][6][7] Today, with a worldwide BMT history of more than 30 years, hepatitis C in longterm survivors requires special attention. The aims of this study were: to determine the prevalence of the HCV antibody in patients who are alive 10 years or more after BMT at the Hospital de Clı´nicas of the Federal University of Parana´(HC-UFPR), to define the annual progression rate of hepatic fibrosis in those patients, and to detect liver cirrhosis among patients who are positive for the HCV antibody.…”
mentioning
confidence: 99%